STRATEGI KOMUNIKASI PEMBANGUNAN RIAU WOMEN WORKING GROUP DALAM MENGGEMBANGKAN KETERAMPILAN ANYAMAN MASYARAKAT DESA PANGKALAN GONDAI KECAMATAN LANGGAM KABUPATEN PELALAWAN - Siti Nur Aisyah; Rusmadi Awza (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2016)
Riau Women Working Group community development consortium under the auspices of the Foundation Tesso Nilo, funded by (TFCA- Sumatra) with various programs one of Handicrafts. Riau Women Working Group do developing in Pangkalan Gondai village because people squeezed from various parties such as companies, forest areas that prevent people from developing a rural region with deforestation, in addition, economic factors gondai village base left behind from other villages. Then, performed the development community was woven handicrafts. This was done for research purposes (1) Knowing the development of communication strategies Riau Women Working Group in developing the handicrafts woven(2) Knowing the process diffusion of innovations woven crafts (3) Knowing the supporting factors in developing the woven handicrafts.This research used descriptive qualitative method, Diffusion of Innovation Theory of Rogers and Shoemaker. There were some of data collection technique was used ;observation, interview, and documentation. Informants selected with purposive sampling technique that was by selecting informants who have the capacity and ability to provide information needed. Informants consisted of the Director of Women Working Group Lists, Staff Field Base Village Gondai, Head of Women, People who follow woven craft. From these results, the researchers concluded that the development of communication strategies Riau Women Working Group was to use newslater media, catalogs and the internet. Instructional design strategy, with training woven handicrafts. Strategies of participation by sending field staff and marketing to various audiences. 2). The process of diffusion of innovation started the development program Riau Women Working Group based non timber forest products, and convey using media newslater, blogs, and catalogs, as well as interpersonal communication directly to the public, with a term of over three years to villagers pangkalan gondai. 3). Factors supporting in developing skills, attributes of innovation that was used, the type of decision, communication channels, the condition of the social system, the role of agent changing.Keywords: Communication Strategy Development, Riau Women Working Group, Woven In Developing.